Governance and performance in public and non-profit organizations - Hinna, Alessandro; Gnan, Luca.; Monteduro, Fabio (Bingley, U.K. : Emerald, 2016)
Studies in Public and Non-Profit Governance (SPNPG) publishes double-blind peer reviewed articles in a growing area of governance research. The series focuses on the 'micro' level of governance in public and non-profit sector. Compared to the wider debate on corporate governance in the private sector and to the literature on the 'macro' and 'meso' levels of governance in the public sector, the organizational (micro) level of governance remains a neglected area of governance in the public and non-profit sector. Therefore, governance systems, mechanisms and roles are primarily investigated at organizational level. SPNPG allows for the establishment of an engaged community of researchers very active in the field. It aims to contribute to the definition of the theoretical components that assign an innovation role to governance systems in public and non profit organizations. It also highlights the opportunity for a deeper analysis of governance mechanisms in their relationships with both the external (stakeholders) actors and the internal (management) actors and address the conditions which enable governance mechanisms to effectively cover their own roles.
Popular reporting and public governance: the case of "Bilancio in Arancio" in Milan municipality / Carmela Barbera, Elio Borgonovi, Ileana Steccolini -- Governance and corruption in the public sector: an extended literature review / Fabio Monteduro, Alessandro Hinna, Sonia Moi -- Exploring board conflicts in public organizations: sources, nature and effects / Andrea Tomo, Danila Scarozza, Alessandro Hinna, Ernesto De Nito, Gianluigi Mangia -- Management control, accountability and learning in public sector organizations: a critical analysis / Max Visser -- Governance of innovation support activities / Johan Wallin -- How board and CEO characteristics can affect Italian and Canadian nonprofit financial performance / Laura Berardi, Michele A. Rea, Giulia Bellante -- From governance to action: measuring the engagement of active stakeholders in the social enterprise / Rita Bissola, Barbara Imperatori -- Interrogating the unilateral influence of transformational leadership: top-down to bottom-up individualized consideration in the board-executive director relationship / Gregory Bott -- Fostering orientation to performance in nonprofit organizations through control and coordination: the case of corporate foundations and founder firms / Marco Minciullo -- Literature review: measuring and assessing organizational performance for non-profits, contextually sensitive standards and measures for the non-profit organization / Lisa Morrison.
Includes bibliographical references.
Print version record
Keywords: Political Science -- Public Policy / Regional Planning; Corporate governance & responsibilities; Public administration; Corporate governance